Algunas reflexiones sobre la representación del tiempo en la imaginería maya antigua - Erik Velásquez García (Journal de la Société des Américanistes)
This work registers and explores some of the many strategies that Mayan artists of the Classic period (AD 250-900) used to represent or suggest the flow of time: the containment of sculptural volumes, the manipulation of dates, the conventional distribution of figures in the pictorial field, the juxtaposition of different times and spaces, the simultaneous angles of view, the displacement between causes (indicated in the texts) and their effects (represented in the images), the sequence in praesentia, the sequence in absentia, and the peripeteia or eloquent instant that suggests psychologically the feeling of change or turning. The common denominator of all these means is the intimate union between time and space, as two aspects of the same reality, where the narrative flow implies the idea of chronological sequence, but also of spatial ordering.